COVID 19: the impact of government policy responses on economic activity and stock market performance in Malaysia - Keh, Chia-Guan; Tan, Yan-Teng (Penerbit Universiti Kebangsaan Malaysia, 2021)
The exponential spread of the coronavirus in Malaysia has caused a significant majority of the economic activities to cease, resulting in poor stock market performance. This pandemic situation has in turn prompted the government to introduce policies to restart and improve economic activity and stock market performance. Hence, does the government’s interference in attempting to control the outbreak of COVID-19 disease, play an important part in affecting the level of economic activity and stock market performance? To resolve this doubt, the impact of government policy responses to COVID-19 in the case of Malaysia was investigated. The sample period of the study was from 28 January 2020 till 29 May 2020, amounting to a total of 84 observations. The findings reveal that the responses taken by the government, such as staying at home requirements, closure of workplaces and debt or contract relief for households, significantly affected both economic activity and stock market performance in the country. Based on the results, these responses appear to have significant policy implications, particularly in displaying that debt or contract relief for households have negative impacts on the economic activities, but a positive impact on the stock market.